2016
DOI: 10.1007/s13365-016-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-associated release, uptake, and neurotoxicity of HIV-1 Tat protein

Abstract: HIV-1 Tat is an indispensible transactivator for HIV gene transcription and replication. It has been shown to exit cells as a free protein and enter neighboring cells or interact with surface receptors of neighboring cells to regulate gene expression and cell function. In this study, we report, for the first time, exosome-associated Tat release and uptake. Using a HIV-1 LTR-driven luciferase reporter-based cell assay and Western blotting or in combination with exosome inhibitor, OptiPrep gradient fractionation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 135 publications
1
50
0
Order By: Relevance
“…Exosomes appear to be an important carrier of HIV-1 RNA (Columba Cabezas and Federico 2013) and HIV proteins, such as Gag, Nef (Booth et al 2006) (Lenassi et al 2010) or Tat (Rahimian and He 2016), although a recent report questioned the idea that Nef can be transferred intracellularly by exosomes (Luo et al 2015). Nevertheless, Nef mRNA and Nef protein were found in plasma exosomes of patients with HIV-associated dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes appear to be an important carrier of HIV-1 RNA (Columba Cabezas and Federico 2013) and HIV proteins, such as Gag, Nef (Booth et al 2006) (Lenassi et al 2010) or Tat (Rahimian and He 2016), although a recent report questioned the idea that Nef can be transferred intracellularly by exosomes (Luo et al 2015). Nevertheless, Nef mRNA and Nef protein were found in plasma exosomes of patients with HIV-associated dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids, cocaine and METH are highly addictive and all seem to be able to influence gene expression in neural and immune cells via mechanisms that involve short, con-coding, regulatory microRNAs and compromise control of HIV infection as well as normal neuronal function [19,245]. Moreover, accumulating evidence suggests a critical role for exosomes, globular, membranous extracellular nanovesicles in HIV infection, HAND and also drug abuse-related neurodegenerative diseases [246,247,248,249]. A detailed discussion of the additional abused substances, microRNAs and exosomes is beyond the scope of this review, but those areas of research are poised to significantly contribute to our understanding of the combined effects of HIV + cART + abused drugs on the brain and may help to develop future, improved therapies for addiction and HAND.…”
Section: Neuronal Injury By Hiv + Cart + Methmentioning
confidence: 99%
“…We have demonstrated that Tat specifically binds to low-density lipoprotein receptors on neurons, which leads to Tat neuronal uptake in its biologically active form (Liu et al 2000). Using primary astrocytes from iTat mice, a HIV-1 LTR-driven luciferase reporter-based cell system and a well-defined OptiPrep-based exosome purification protocol, researchers showed that Tat was secreted in exosomes, which were potently neurotoxic (Rahimian and He 2016a). These findings indicated that a significant fraction of Tat is secreted in the form of exosomes and may contribute to the stability of extracellular Tat and broaden the spectrum of its target cells.…”
Section: Use Of Itat Mice In Studies Of Tat Neurotoxicity and Its Molmentioning
confidence: 99%